2022
DOI: 10.15537/smj.2022.43.2.20210720
|View full text |Cite
|
Sign up to set email alerts
|

Indices of insulin resistance and adiposity can detect obesity-related morbidity in pediatrics

Abstract: Objectives: To evaluated obesity-related morbidity prevalence among overweight/obese children and adolescents in Saudi Arabia, adiposity indicators and insulin resistance as obesity-related morbidity predictors. Methods:We enrolled 318 overweight/obese children attending a Pediatric Endocrinology Clinic at King

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Similar results were found by Faria et al ( 17 ) in Brazilian adolescents and by Vásquez et al ( 18 ) in a cohort of Chilean children aged 4, 7, and 10 years; however, in both studies, not all the participants were overweight. The observation of a moderate correlation between body fat and HOMA-IR was also observed in a study of overweight Saudi Arabian children and adolescents aged between 2 and 20 years ( 19 ). Excess body fat can lead to metabolic changes, including inflammatory mechanisms, which increases insulin resistance and may help to partially explain this finding.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Similar results were found by Faria et al ( 17 ) in Brazilian adolescents and by Vásquez et al ( 18 ) in a cohort of Chilean children aged 4, 7, and 10 years; however, in both studies, not all the participants were overweight. The observation of a moderate correlation between body fat and HOMA-IR was also observed in a study of overweight Saudi Arabian children and adolescents aged between 2 and 20 years ( 19 ). Excess body fat can lead to metabolic changes, including inflammatory mechanisms, which increases insulin resistance and may help to partially explain this finding.…”
Section: Discussionsupporting
confidence: 52%
“…In BFP analyses, the cutoff point <34% of body fat may be able to rule out changes in HDL-c (high specificity), while the cutoff point > 36.6% may be able to predict changes in the HOMA-IR index (high sensitivity). In the study by Abdelhamed et al ( 19 ), a cut-off of 46.1% of BFP was shown to have the best sensitivity/specificity ratio for detecting obesity-related morbidities in Saudi children and adolescents. The joint analysis of several biochemical parameters (grouped as “obesity-related morbidities”) to estimate the accuracy of the BFP in predicting laboratory changes in overweight individuals may have contributed to the difference between the Saudi work and the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[ 28 ] and indirectly suggest a decrease in insulin sensitivity due to the increased IR reported by Abdelhamed et al . [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Joseph et al [ 30 ] reported that HOMA-IR was positively correlated with BFM and WC, and Rajesh et al [ 20 ] reported that HOMA-IR was positively correlated with BFM. Marwa et al [ 31 ] stated in their study that BMI and WC had significant AUCs in predicting IR in obese children and adolescents, and that BMI had the highest sensitivity and WC the highest specificity.…”
Section: Discussionmentioning
confidence: 99%